On the Fluctuations of Entries of Matrices whose Randomness is due to Classical Groups - Vasilchuk, V. (Журнал математической физики, анализа, геометрии, 2014)
We consider first the n x n random matrices Hn = An +Un*BnUn, where An and Bn are Hermitian, having the limiting normalized counting measure (NCM) of eigenvalues as n →∞, and Un is unitary uniformly distributed over U(n). We find the leading term of asymptotic expansion for the covariance of elements of resolvent of Hn and establish the Central Limit Theorem for the elements of suffciently smooth test functions of the corresponding linear statistics. We consider then analogous problems for the matrices Wn = SnUn*TnUn, where Un is as above and Sn and Tn are non-random unitary matrices having limiting NCM's as n →∞. Рассмотрены сначала n x n случайные матрицы вида Hn = An +Un*BnUn, где An и Bn - эрмитовы, имеющие предельную нормированную считающую меру (НСМ) собственных значений при n →∞, и Un - унитарные, распределенные равномерно по U(n). Найден ведущий член асимптотического разложения ковариации элементов резольвенты Hn и доказана Центральная Предельная Теорема для элементов достаточно гладких тестовых функций соответствующих линейных статистик. Затем аналогичные задачи рассмотрены для матриц вида Wn = SnUn*TnUn, где Un такая же, а Sn и Tn - неслучайные унитарные матрицы, имеющие предельные НСМ n →∞.